Research of test method for ski-jump takeoff which is based on BP neural network and multi-factor weight analysis - Liu, Miaoxin; Yuan, Zhengting; Liu, Tao (Journal of physics. Conference series, 2023)
Ski-jump takeoff of carrier-based aircraft is a very risky subject. At present, the principle, characteristics and influencing factors of ski-jump takeoff are mainly studied at home and abroad, but there is no relevant research on how to carry out ski-jump takeoff test and related risk control. To ensure smooth and safe ski-jump takeoff testing, this paper first determines the influencing factors of ski-jump takeoff based on the dynamics model. Secondly, based on the BP neural network, the corresponding relationship between the influencing factors, the angle of attack and the lifting speed is established. Finally, the quantitative analysis conclusion of the influencing factors is obtained according to the multi-factor weight analysis method and put forward the design method takeoff under the combined conditions of “weight-center of gravity-inertia-configuration” and the test risk control measures, which provides methods and ideas for the safety of ski-jump takeoff test.